Study on antioxidants extraction from oak bark and their use for oxidation stability of sunflower oil - Demydova, Anastasiia; Nosenko, Tamara; Bakhmach, Volodymyr; Shemanska, Evgenia; Molchenko, Svitlana (My University, 2021)
Suitable conditions of oak bark polyphenols extraction were developed in this study in order to use them as inhibitors of vegetable oil oxidation. It was shown that polyphenols of oak bark were effective as natural inhibitors of oil oxidation. It had been demonstrated that use of food acids in combination with a water-alcohol solvent and microwave field were effective for the enhancing of the extraction process of oak bark. The method of creation of the stable fat and hydrophilic antioxidants containing system was developed

У цьому дослідженні розроблено відповідні умови екстракції поліфенолів кори дуба з метою використання їх як інгібіторів окислення рослинної олії. Було показано, що поліфеноли кори дуба ефективні як природні інгібітори окислення нафти. Показано, що застосування харчових кислот у поєднанні з водно-спиртовим розчинником і мікрохвильовим полем є ефективним для посилення процесу екстракції кори дуба. Розроблено метод створення стабільної системи, що містить жир і гідрофільні антиоксиданти
Keywords: кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; oak bark; antioxidants; induction period of oil oxidation; ultra-disperse system; кора дуба; антиоксиданти; індукційний період окислення олії; ультрадисперсна система